REKONSTRUKSI PEMIKIRAN FIKIH: Suatu Gagasan Awal Mencairkan Kebekuan Fikih di Indonesia - Muhtadin Dg. Mustafa (Hunafa: Jurnal Studia Islamika, 2011)
Indonesia is a country  whose population is majority Muslim. Thus, the aspects of syari’ah (Islamic law) should color the religiousity of Indonesian Muslims. However, the syari'ah is not static, it is  dinamic as it always  gets in contact with social aspects. In this context, the reactualization and reconstruction of Islamic  jurisprudence should be continually performed. The reactualization of the Islamic jurisprudence related to pragmatic values covering the patterns  of  daily life of the Muslims while the reconstruction the Islamic jurisprudence thought more focuses on conceptual intellectuality values. Based on the  relationship of  the idea of  reactualization and reconstruction of the Islamic jurisprudence, it can be concluded that the latter is an infrastructure, while the renewal is a means to realize the function of  syari'ah (Islamic law) as a social control and social engineering.